'In heavy rotation': uncovering the phonographic industry and the 'NGOMA national label' in socialist Mozambique (1978–1990). Issue 1 (2nd January 2023) - de Freitas, Marco Roque
ABSTRACT: This article outlines the structure and editorial practices of the phonographic industry in postcolonial Mozambique during the so-called 'socialist period'. It details the production phases, the associated companies and delves into the material conditions and aesthetic values that guided the phonograms published by NGOMA—dubbed as 'the Mozambican national label'—and their relationship with state-defined cultural policy between 1978 (when production on this series commenced) and 1990 (when vinyl production officially ceased in the country). Several themes are explored, such as predominant topics of song lyrics, repertoires and artists, copyright, women artists, and the restrictions on music production during the civil war. After analysing the main musical trends and acknowledging noteworthy absences, I reflect on NGOMA's efficiency in the nation-building process.